CAPN5 attenuates cigarette smoke extract-induced apoptosis and inflammation in BEAS-2B cells - Herui Li; Yiming Ma; Tiao Li; Zihang Zeng; Lijuan Luo; Xiangming Liu; Yi Li; Yan Chen (Tobacco Induced Diseases, 2024)
Introduction Apoptosis and chronic inflammation are the main phenotypes in chronic obstructive pulmonary disease (COPD) pathogenesis. Cigarette smoke exposure is the leading risk factor for COPD, which causes aberrant airway epithelial structure and function. As a non-classical calpain, the molecular function of calpain5 (CAPN5) in COPD remains unclear. This study investigated the role of CAPN5 in mediating cigarette smoke extract (CSE)-induced apoptosis and inflammation.